An international study of pro/antisocial behavior in young adults - Pereira, Miguel Basto (2019)
This article presents an international study of pro/antisocial behavior in young adults (SOCIALDEVIANCE1820). This is an ongoing cross-continental longitudinal research project that includes data and researchers from multiple countries across five continents. It aims to explore the intercultural universality of the risk and protective factors associated with pro/antisocial behavior and psychosocial adjustment during early adulthood. Researchers from all countries involved have already translated their questionnaires, selected an appropriate team, and started the data collection process. It is expected that this intercontinental longitudinal research project will have a tremendous social and scientific impact; this study will allow researchers to overcome many limitations of previous meta-analyses, such as limiting the applicability of data to developed countries and the bias caused by combining different assessment methods. Challenges in implementing cross-national studies, and the importance of this type of study to global policies, are discussed.